Parallel Evolution by Gene Duplication in the Genomes of Two Unicellular Fungi - Hughes, Austin L.; Friedman, Robert

(untitled) (Genome Research, 2003)
Phylogenetic analysis of conserved gene families in fission yeastSchizosaccharomyces pombe and brewer's yeastSaccharomyces cerevisiae showed that gene duplications have occurred independently in the same families in each of these two lineages to a far greater extent than expected by chance. These species represent distinct lineages of the phylum Ascomycota that independently evolved a “yeast” life cycle with a unicellular thallus that reproduces by budding, and many of the genes that have duplicated independently in the two lineages are known to be involved in crucial aspects of this life cycle. Parallel gene duplication thus appears to have played a role in the independent origin of similar adaptations in the two species. The results indicate that using phylogenetic analysis to test for parallel gene duplication in different species may help in identifying genes responsible for similar but independently evolved adaptations.